Análise espacial das taxas de mortalidade por atropelamento dos municípios paulistas utilizando ferramentas de estatística espacial - Ferreira, Ana Cristina Maurício (Universidade Federal de São Carlos, 2007)
The Brazil presents exalted indexes of accidents and constitute one of bigger problems of public health, leaving in year, thousands of deads or peoples with temporaries or permanencies deficiencies. It is necessary to consider that big piece of accidents occurred in the country are trampling down, been that your mortality also presents raised numbers. In Brazil occur approachment 5,6 deaths for 100 thousand habitants in year. The São Paulo State presents numbers very higher at national average, of nine deaths for 100 thousand habitants. Many municipality of São Paulo State presented, in year s 2005, indexes higher at 20 deaths for 100 thousand habitants. Considering that are not many the research that discuss specified of problem of trampling down, this work can be interesting with intension of to help your understanding and identify possible contributing factories for your incident. This research had for mainly objective to analyze the incident of deaths for trampling down in the municipalities of São Paulo State, considering that discuss of a spacious phenomenon, where the localization is a important attribute, permitting so, the search for existence of stone of distribution, tendency and dependence spacious. For this been utilized implements of GIS and of spacious statistics. Was understandied that the São Paulo State presents three groupment of area with clusters, localized in the region northwest/ centre-west, south-east and south of State. Presents also correlation spacious signified with some indicates studieds like the case of demography density, populational increase, age of population, level of urbanization, municipalities and index of motorization. Also is necessary be considered that the trampling down can be associate with factors specified of each municipalities, like the less structure adequate that permit a secure circulation of pedestrian as much urban place as in the highway.
Keywords: Acidentes de trânsito; Estatística espacial; Atropelamento; Análise espacial (Estatística); Sistemas de informação geográfica; ENGENHARIAS